Lemierre Syndrome Associated with Streptococcus constellatus and Atypical Vascular Involvement: A Case Report and Review of the Literature - Luca Pipitò; Antonio Anastasia; Fabrizio Passalacqua; Giulio D’Agati; Floriana Di Figlia; Benedetta Romanin; Silvia Bonura; Raffaella Rubino; Agostino Inzerillo; Caterina Sarno; Antonio Cascio (Infectious Disease Reports)
Background: Lemierre syndrome is a rare and life-threatening disease. It is characterized by septic thrombophlebitis of the internal jugular vein, historically associated with Fusobacterium necrophorum infection. However, atypical cases and associations with other organisms have been reported. Methods: Here, we describe a challenging case of Lemierre syndrome in a 71-year-old woman caused by Streptococcus constellatus and review the related literature. Case: The patient experienced multiple hospital admissions due to misdiagnoses and developed thrombosis involving the internal jugular vein and transverse sinus bilaterally, pulmonary complications including the formation of a pseudoaneurysm, and occipital abscess. She presented with headaches, neck pain, and blindness. Prolonged antibiotic therapy was administered, leading to gradual improvement of symptoms, with partial resolution of blindness. Prophylaxis with intramuscular penicillin was prescribed at discharge. Conclusions: Our case underscores the importance of considering Lemierre syndrome in patients who present with multiple thrombotic events affecting the intracranial circulation and/or jugular veins, particularly in those already receiving anticoagulation therapy or with no identifiable cause for thrombosis, even in the absence of sore throat or fever.